The adventures of Marco Flamingo in the jungle - Jarkins, Sheila (Raven Tree Press, 2011)
Marco Flamingo celebrates his birthday at home with friends such as Whale and Dolphin but his birthday wish for adventure is fulfilled by Elephant's invitation to spend a day with him in the jungle.